Uncommon Presentation of a Common Histiocytic Tumor: A Rare Entity - Kar, Chinmay (Indian J Dermatol, 2015)
Juvenile xanthogranuloma (JXG) is the most common form of non-Langerhans cell histiocytic lesion, characterized by benign, usually asymptomatic, self-healing yellowish brown papulonodular lesions of skin and other organs in the absence of metabolic disorder. The cells of origin of JXG are dermal dendrocytic cells. Histopathologically there is dermal infiltration of foamy or non-foamy histiocytes with or without giant cell. Immunohistochemistry shows CD68 positivity with CD1a and S-100 negativity of lesional cells although S-100-positive JXG have been reported. JXG may be associated with neurofibromatosis type one (NF 1) with increased risk of juvenile chronic myelogenous leukemia and other hematological malignancies. Our case was S-100 immunoreactive multiple, cutaneous JXGs with NF 1 without any visceral involvement or malignant complication. We are presenting this case due to its rarity.